Network approach to constructing theory of participation in spatial planning. (December 2018) - Lovrić, Nataša; Lovrić, Marko
Highlights: Initial theory of participation in spatial planning is developed. Grounded theory approach is standardized through social network analysis. Data is grounded in spatial planning of Nature Park Medvednica, Croatia. Culture of spatial planning promotes professional expertise over participation. Abstract: Although importance of participation in public decision making is widely recognized in policy sciences, there is no consensus on what its preferred role and meaning would be. In the practice of European spatial planning, its outcome - impacts are peripheral, and there is no distinct theoretical explanation underpinning why this is so, and how the situation may be altered. The primary aim of the study is to tackle this issue; by developing initial step towards a theoretical explanation of participation in spatial planning. The inductive analysis is based on such process for the Nature Park Medvednica, a protected area in Croatia affected with strong urbanization. The research design is based on grounded theory, an approach for developing theoretical explanations of a given phenomenon by gathering qualitative data rooted in practical case(s), where the explanation is decontextualized and thus universal enough that it can be used in other cases (i.e. generalized). However, there is a high level of inconsistency on how exactly grounded theory should be applied, which diminishes the validity of its claims. The secondary aim of the study is to provide structure to how grounded theory could be applied; by developing a series of methodological steps rooted in social network analysis, and thus enhancing its replicability. Primary data is drawn from 56 interviews, covering a 30-year process of spatial planning. On a practical level, the results demonstrate that the role of participation in spatial planning for Nature Park Medvednica does not substantially differ from other comparable cases, where it starts late in the process and has mostly a symbolic role. On a theoretical level, a series of highly general, decontextualized codes have been developed, such as classification of actors, forms of participation and of system that suppresses its prominence. The research also identifies some policy solutions on how to alter the situation; for an individual process of spatial planning, disempowered groups can substantially affect the outcome only through public political engagement, which in turn is affected by 'calculation' of personal costs and benefits of participation. On a more general level, the change of the role of participation in spatial planning of a given local setting can occur through the following modes: (I) change of power relations between (construction) interest groups and the administration that leads the process, and (II) change in how the 'value' of a spatial plan is perceived by the administration that leads the process - from a system that promotes professional expertise and human-centered values to a system which endorses participation of the 'lay', de-values formal expertise, and perceives that nature has a value on its own, independent from human needs.